Excitation of gap plasmonic wavguides by nano antennas - Schmauß, Bernhard; Weng, J.; Banzer, P.; Ploss, D.; Kriesch, A.; Peschel, Ulf (Conference on Lasers and Electro-Optics CLEO, Paper QMF1, San Jose, May, 2010)
We experimentally demonstrate the excitation of plasmonic gap waveguides by nano antennas. The excitation is shown to be both spatially and spectrally dependent which can potentially be used for the selective excitation of plasmonic nanostructure
lhft_intern.bib::Schmauss10